EDUKASI BREAK EVEN POINT (BEP) PADA PELAKU UMKM KULINER DI KOTA PAREPARE - Sudirman, Sudirman; Nur, Muhammad (Media Literasi Indonesia, 2025)
A Micro, Small, and Medium Enterprises are a sector that plays a vital role in the national economy. One area with significant potential for MSME development is Parepare City, South Sulawesi Province. UMKM in the culinary sector in Parepare still face various obstacles, particularly in the management and financial planning aspects of their businesses. One important indicator in business financial planning and management is an understanding of the Break Even Point (BEP) concept. The purpose of this PKM is to increase the knowledge of Culinary UMKM regarding Break Even Point (BEP). The activity was held on Monday, August 18, 2025, at The Taman Cafe, Parepare City, from 4:00 PM to 6:00 PM WITA. The activity was attended by 12 culinary UMKM. The activity began with a pre-test given to all participants. The next activity was a BEP education activity delivered by the Team Leader (Sudirman), followed by a post-test given to all participants. The activity concluded with a short question and answer session, participant reflections, and documentation in the form of a group photo between the team and participants. The conclusion of the activity is that this Community Service activity is that the Education activity effectively increases the understanding of culinary MSME actors regarding the Break Even Point (BEP) concept, as evidenced by the significant increase in post-test scores compared to the pre-test.